Legal regulation of consumer relinquishment of the contract: Comparative analytical study - Saed Mine, Rawa Kaka Rash (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
The multiplication of the types of sales (selling and buying), activities and the tremendous technological development in the production and marketing of goods and services made the consumer confused which face the contract problems and makes the sales unstable. There is no doubt about the need to protect consumer satisfaction; especially when the general rules are unable to keep pace with this development and provide the necessary amount of protection to the consumer. Renunciation of the contract is a means to consumer which is proved by law or agreement. During it, the consumer is allowed to revoke the commitment that was previously associated with his sole will, During a certain period without reason and without consideration. It is not usually permitted. This prompted many legislations to explicitly state that consumers are allowed to waive the contract. It has also set controls for it but they have different attitudes about its decisions in general. And that’s according to the goals that desired by each legislation. Accordingly, the subject of the research is the legal regulation of the consumer’s revoke from the contract, which aims to identify the revoke and its provisions in the legislations of the subject of the research. And see the attitude of the Iraqi consumer protection law about it. It has been relying on the comparative analytical approach in it. The research has found out the revoke is a choice to the consumer and it is closer than the vision option but it is a vision choice in another form. The legislations have limited its domain by take out some cases in their areas. So that the prescribed protection for the consumer is not on the right of the professional. As well as, a period has been set for the consumer to practice the revoke to stabilize for transactions. The Egyptian law has given more freedom to consumer by putting an option between refunding the price and exchanging commodity with another. Iraqi consumer protection law has a special attitude. That’s in a case that the professional does not inform the consumer. In fact, it is closer to applying general rules, rather than being a revoke as an exact meaning.